Application of Indigenous AMF from ex-coal Mining Soil Combined with Phosphorus Fertilizers to Improved Oil Palm Seedling Growth (Elaeis guineensis Jacq.) - Duaja, Made Deviani; Kartika, Elis; Lizawati, Lizawati (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
Opencast mining caused heavy deforestation and barren land in Jambi. This ex-mining land must be reclaimed by planting crops based on biofertilizers containing mycorrhizae, this is a potential alternative that provides benefit both agronomy plant and ecosystem specially replanting with oil palm. Those are the technology for reclamation ex-coal mining soil. This research aim is to examine the effect of four combinations indigenous isolate of Arbuscular Mycorrhizae Fungi (AMF), which is originated from ex-coal mining soil that combined with Phosphorous fertilizers to minimize utilizing P fertilizer at oil palm pre-nursery, to improve soil fertility, and seedling growth. Hence, this research was arranged in factorial experiment with 2 factors, using a complete randomized design with three replications. The first factor is five different mycorrhizae isolates, representing a broad range of endomycorrhizae fungi, there are: without indigenous AMF, isolate of Glomus sp. 3, isolates of Glomus sp. 6, isolates of Glomus sp. 15 and isolates of Glomus sp. 16. The second factor is P fertilizer: control (without P fertilizers), fertilizer dosage P 25%, 50%, 75%, and 100%. Variables measured are shoot height, number of leaves per plant, total leaf area per plant, and plant stem diameter. The data were analyzed by analysis of variance to see whether there was an interaction between the MVA isolate and the P fertilizer dosage. The result showed a significant effect on palm oil seedling growth, shoot height, number of leaves per plant, total leaf area per plant but there is no interaction on the stem diameter. Plants that are inoculated with mycorrhizae have greater P content in leaves than those not inoculated. The types of isolated Glomus sp.3 and dosage P 75% of recommended dosage, give the best seedling growth. This research concluded that inoculation with AMF could minimize P fertilizers doses.